Sistem Pengelolaan dan Strategi Pemasaran Event Pariwisata di Nusa Dua - Yusfi Azizur Rohman; Rebecha Prananta (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2019)
Abstract Events are activities consist of transient, and every event is a unique blending of its duration, setting, management, and people. The aim of research are describe management of monthly and weekly event and marketing strategyoturism at Nusa Dua. The result are that event gathering financial, image and experiences. As the tourists are Nusa Dua organizer have hold the event by monthly and weekly based on theme and kind of event. Every event use rental space and ticket. Guidanceform the Indonesia Tourism Development Corporation the tarketing strategy to increasing tourists to visits Nusa Dua area are use flyer, baliho, roadshow, presentation and posting at social media (instagram, facebook). Keywords: management system, marketing strategy, tourism